Lead ions encapsulated in liposomes and their effect on Staphylococcus aureus - Kensova, Renata; Blazkova, Iva; Konecna, Marie; Kopel, Pavel; Chudobova, Dagmar; Zitka, Ondrej; Vaculovicova, Marketa; Hynek, David; Adam, Vojtech; Beklova, Miroslava; Kizek, Rene (International journal of environmental research and public health, 2013)
The aim of the study was the preparation of a liposome complex with encapsulated lead ions, which were electrochemically detected. In particular, experiments were focused on the potential of using an electrochemical method for the determination of free and liposome-encapsulated lead and determination of the encapsulation efficiency preventing the lead toxicity. Primarily, encapsulation of lead ions in liposomes and confirmation of successful encapsulation by electrochemical methods was done. Further, the reduction effect of the liposome matrix on the detected electrochemical signal was monitored. Besides encapsulation itself, comparison of toxicity of free lead ions and lead ions encapsulated in liposome was tested. The calculated IC50 values for evaluating the lead cytotoxicity showed significant differences between the lead enclosed in liposomes (28 µM) and free lead ions (237 µM). From the cytotoxicity studies on the bacterial strain of S. aureus it was observed that the free lead ions are less toxic in comparison with lead encapsulated in liposomes. Liposomes appear to be a suitable carrier of various substances through the inner cavity. Due to the liposome structure the lead enclosed in the liposome is more easily accepted into the cell structure and the toxicity of the enclosed lead is higher in comparison to free lead ions.
Keywords: Staphylococcus aureus; Liposomes; Spectrophotometry, Atomic; Nanoparticles; Lead; elektrochemické techniky; Electrochemical Techniques; olovo; spektrofotometrie atomová; liposomy; nanočástice